Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset containing 59911 species occurrences available in GBIF matching the query: { "and" : [ "Country is Belgium", "TaxonKey is one of (Aponogeton distachyos L.f., Cabomba caroliniana A.Gray, Cherax destructor Clark, 1936, Crassula helmsii (Kirk) Cockayne, Elodea densa (Planch.) Casp., Erythranthe guttata (DC.) G.L.Nesom, Faxonius immunis (Hagen, 1870), Faxonius juvenilis (Hagen, 1870), Faxonius rusticus (Girard, 1852), Faxonius virilis (Hagen, 1870), Heracleum mantegazzianum Sommier & Levier, Heracleum persicum Desf., Heracleum pubescens (Hoffm.) M.Bieb., Houttuynia cordata Thunb., Hydrocotyle ranunculoides L.f., Impatiens glandulifera Royle, Koenigia polystachya (Wall. ex Meisn.) T.M.Schust. & Reveal, Lagarosiphon major (Ridl.) Moss, Ludwigia grandiflora (Michx.) Greuter & Burdet, Ludwigia peploides (Kunth) P.H.Raven, Lysichiton americanus Hultén & H.St.John, Myriophyllum aquaticum (Vell.) Verdc., Myriophyllum heterophyllum Michx., Petasites japonicus (Siebold & Zucc.) Maxim., Pontederia cordata L., Procambarus acutus (Girard, 1852), Procambarus clarkii (Girard, 1852), Procambarus virginalis Lyko, 2017, Saururus cernuus L., Zizania latifolia (Griseb.) Hance ex F.Muell.)", "OccurrenceStatus is Present", "Year is greater than or equal to 2000" ] } The dataset includes 59911 records from 47 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0013684-230530130749713/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences